Kyle V Singer - drawing and new media - Kyle, Singer, author (Colorado State University. Libraries, 2017)
I highlight the importance of flaws, trauma, and repression by evoking concepts of “the unconscious” through surrealist methodologies. Considering all that is suppressed/repressed within my psyche to form the culturally accepted version of myself, and by examining the distance between my identity, and the repressed self. Engaging the viewers through superabundance, tackling issues of consumerism with construction that grapples with the excess of daily life. I question aesthetic value, moral responsibility, and political agency in my efforts to sublimate the abject. The abject touches on the fragility of our boundaries and the spatial distinction between our interiority and exteriority. My art stems from an insatiable appetite for new materials and compulsive ways I can explore new methods and processes. The impetus for my work is a cultural and political critique imbued with my own flavor of cynicism and disillusionment. I endeavor to destabilize perceptions by creating overwhelming masses of matter and meaning; meant to be all-consuming. This non-hierarchical kind of making causes a slow unraveling of my work allowing for an unpredictable composition and use of materials.

The abject deals with a vast array of issues such as marginalized people, mortality, boundaries, and repulsion. It is usually used to describe the human reaction to horror and threatens to breakdown meaning by causing the loss of distinction between subject and object; between self and other. In an era of mass displacement due to natural and political disasters, this conceptually interest me and seem particularly relevant. The abject calls into question hierarchical values that allows for the dispersion and displacement of people: whether it be refugees, or low in-come families pushed out by gentrification. In the age of information, we have become incredibly efficient at codifying people and separating them from their personhood and seeing them only as replaceable objects with a set value; as a cluster of information to be used and exploited for profits. I plan to continue exploring the possibilities of media combination and new technologies. I am currently working with laser cutting, 3D printing, 3D scanning and the CNC machine. I am trying to explore new ways of misusing the machinery as a chance operation that allows the ebbs, flows, and limitations of the process itself to become a way of making. These new processes drastically change the way we think about construction and the possibilities of form. It blurs the boundaries between the hand-made and the mass-produced, dovetailing nicely with my ideas of consumerist cultural critique.
An act of cathartic expression that abreact trauma through sublimation
005 - Kyle Singer
Keywords: art; new media; drawing